Review: synthetic polymer hydrogels for biomedical applications - Gibas, Iwona; Janik, Helena (Publishing House of Lviv Polytechnic National University, 2010)
Synthetic polymer hydrogels constitute a group of materials, used in numerous biomedical disciplines, and are still developing for new promising applications. The aim of this study is to review information about well known and the newest hydrogels, show the importance of water uptake and cross-linking type and classify them in accordance with their chemical structure. Синтетичні полімерні гідрогелі являють собою групу біоматеріалів, які вже використовуються в чисельних біомедичних галузях, і які розробляються для нового перспективного застосування. В роботі проаналізовано інформацію як про відомі, так і новітні гідрогелі. Показано, наскільки важливими є здатність до водопоглинання і тип структурування, а також проведено класифікацію гідрогелів відповідно до їх хімічної структури.
Огляд: синтетичні полімерні гідрогелі для біомедичного застосування
Keywords: polymer; hydrogel; biomaterial; biomedical polymer; polymer hydrogel; полімер; гідрогель; біоматеріал; біомедичний полімер; полімерний гідрогель